In vivo Pharmacokinetic Drug-Drug Interaction Studies Between Fedratinib and Antifungal Agents Based on a Newly Developed and Validated UPLC/MS-MS Method - Tang, Congrong; Niu, Xiaohui; Shi, Lu; Zhu, Huidan; Lin, Guanyang; Xu, Ren-ai (Frontiers in Pharmacology, 2021)
In the current research experiment, a sensitive, precise and rapid bioanalytical approach involving the detection of fedratinib concentrations in rat plasma by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) technique was optimized and established, and it was employed to describe the changes of fedratinib concentrations after oral treatment with various antifungal drugs (isavuconazole, posaconazole, fluconazole and itraconazole). An Acquity UPLC BEH reverse-phase C18 column (2.1 mm × 50 mm, 1.7 μm) was used for chromatographic separation of fedratinib and bosutinib (as internal standard (IS) in our study) under a linear gradient elution of the mobile phase, which was composed of solution A (acetonitrile) and solution B (water with 0.1% formic acid), along with 0.40 ml/min flow rate. The analyte and internal standard were measured with electrospray ion source in positive ion mode on a XEVO TQS triple quadrupole tandem mass spectrometer. The newly developed UPLC-MS/MS assay displayed enough linearity within the concentration range of 0.5–500 ng/ml for calibration curve. The intra- and inter-day of precision and accuracy were evaluated and validated to meet the requirements for the guidelines of bioanalytical assay. In addition, the findings of matrix effect, recovery, and stability were all within the acceptable limits. The new UPLC-MS/MS method was also successfully applied to characterize the pharmacokinetic changes of fedratinib in rats in the present of different antifungal drugs (such as isavuconazole, posaconazole, fluconazole and itraconazole). It turned out that fluconazole resulted in a prominent inhibitory effect on fedratinib metabolism in rats, followed by treatment with itraconazole and isavuconazole. Therefore, the toxicity of fedratinib should be avoided when the concurrent use of fedratinib with CYP3A4 inhibitors may occur.